2012
DOI: 10.1007/s11010-012-1305-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of cyclooxygenase-2 and matrix metalloproteinases (MMP-2 and MT1-MMP) in human breast cancer tissue

Abstract: Breast cancer (BC) is the most common neoplasm among women in most developed countries, including Egypt. Elevated levels of certain proteins in human BC are associated with unfavorable prognosis and progressive stages of the disease. The aim of our study was to evaluate the protein expression profile and prognostic significance of cyclooxygenase-2 (COX-2), matrix metalloproteinase-2 (MMP-2), MMP-9 and membrane type 1-MMP (MT1-MMP) and their interaction in operable BC patients. The protein expression of COX-2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…In mammary epithelial cells, COX-2 induced an EMT featuring anchorage-independent growth [97]. In human breast cancers, COX-2 was found to induce membranetype 1-MMP and its downstream effector MMP-2 [98], factors important in EMT [99], thus providing a rational mechanism through which COX-2 can promote breast cancer invasion.…”
Section: Cox-2 Is Associated With Breast Cancer Invasion Via Emtmentioning
confidence: 99%
“…In mammary epithelial cells, COX-2 induced an EMT featuring anchorage-independent growth [97]. In human breast cancers, COX-2 was found to induce membranetype 1-MMP and its downstream effector MMP-2 [98], factors important in EMT [99], thus providing a rational mechanism through which COX-2 can promote breast cancer invasion.…”
Section: Cox-2 Is Associated With Breast Cancer Invasion Via Emtmentioning
confidence: 99%
“…The remaining 29 papers were approved through scrutinizing the entire paper. Among the 29 papers, five literatures had no sufficient data to analyze (Remacle et al, 1998;Wang et al, 2002;Casar et al, 2010;Mohammad et al, 2012;Ranogajec et al, 2012). MMP-9 protein expression was measured in serum in five studies (Lepp et al, 2004;Lepp et al, 2005;Mattilaet al, 2005;Quaranta et al, 2007;Sung et al, 2012) and one study measured MMP-9 expression in plasma (Ranuncolo et al, 2003).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…COX‐2 expression in predominantly ER‐negative tumors was shown to lead to Akt‐pathway activation . Regarding prognosis, most, but not all, studies have found an association between high COX‐2 expression and worse prognosis. Whether COX‐2 expression was associated with prognosis in the different studies also depended on tumor characteristics, type of breast cancer treatment, body constitution, and concomitant medications .…”
mentioning
confidence: 99%